The Psychological Skills for The Youth Players of Baghdad Clubs Excellent League Soccer Season 2021-2022 - Talib Jasim, Hayder; Lazim Ali, Assad (Journal of Physical Education, 2023)
The research aimed at applying psychological skills scale for youth soccer players in Baghdad excellent league season 2021 – 2022. The subjects were (240) players; 100 players as construction subjects, 90 players for application. The scale consisted of (24) items distributed in (6) fields. Areas of (the ability to mental visualization, the ability to relax, the ability to Confront anxiety, the ability to Focus attention, the ability to self-confidence, the ability to Achievement motivation), the most important conclusions of the study, it was concluded that the study sample suffers from a weakness in the ability to mental perception, focus attention and achievement motivation. Finally, the researchers recommended the necessity of reinforcing all psychological fields as well as training psychological skills through training programs held by the coach in perpetration phase or competition due to the players need to such high leveled skill, because the football player needs these skills in order to be able to face the difficulties of training and intense competition.